Peningkatan Peran UMKM dalam Peningkatan Ekonomi Masyarakat di Kelurahan Kenjeran, Kota Surabaya - Nabila Raharjo, Atha; Nur Kumala, Gading Berlian Wati; Afifuddin, Achmad Arrizal; Casmiwati, Dewi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The administrative reform of MSMEs in Kenjeran Village, Surabaya City, aims to increase the competitiveness of craft and processed fish products in the area. This study identifies the challenges faced by MSME actors, such as limited market access and capital. The research method used is a descriptive qualitative approach through observation, interviews, and documentation. The results of the study indicate that although MSMEs have great potential, they need innovation in marketing strategies, especially by utilizing social media and e-commerce platforms. In addition, the importance of collaboration between the government, local communities, and MSME actors is also expressed to create an ecosystem that supports sustainable growth.